Analisis User Interfaces Pada Website Kampiun ITTP Dengan Metode Heuristik dan System Usability Scale (SUS) (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Kampiun Digital Learning is a website-based Massive Open Online Course (MOOC) owned by the Telkom Purwokerto Institute of Technology (ITTP), which aims to improve the quality of free non-formal education. Unfortunately, since its initial release until now there has never been an analysis of the user interface itself. Even though there are several problems related to the user interface, such as problems with navigation (search filters), notifications, registration instructions, and basic website guidelines. Based on these problems, it is necessary to analyze the user interfaces on the Kampiun website to see how the sustainability of Kampiun is based on the perspectives of experts and users, the combination of Heuristics and System Usability Scale (SUS) methods in this study was carried out because in their functions they have different but complementary, heuristic focuses. has the perspective of the experts, while SUS has the perspective of the user. This study uses 10 heuristic aspects and 10 SUS questionnaire questions. The purpose of this research is to be able to produce recommendations for improvement from both existing perspectives and identify aspects that need improvement, as well as being useful in helping to find problematic heuristic aspects that must be addressed. The SUS score from the Kampiun website after the calculation is done is 58.4. The results of this study are recommendations on aspects that need to be improved in order to provide a significant increase in the SUS score, several recommendations for improvements that need to be made include clarity of information, use of images, appropriate colors and grammar, consistency of writing, standard writing standards, error message, there is an online guide and a help button.